ANALISIS USABILITY MENGGUNAKAN METODE WEBUSE PADA WEBSITE KITABISA.COM - Andiputra Andiputra; Rinabi Tanamal (Universitas Bunda Mulia, 2020)
Website is a collection of pages that contain information, videos, audio, images and the like that are interconnected with one another and can be accessed today by using a browser that is connected to the internet. Usability is the ability of an application or website that can be used easily to achieve the goals of the user itself. Why usability is important if an application or website has good usability, the user will be able to easily use it, besides easy to use usability must also be easy to learn by the new user and of course the application or website must run according to its function and no errors occur when the user uses it. Surely this usability has become standard at ISO 9241-11: 2018. Every website has its own usability level, the higher its usability value, the better the usability value means that the application or website is easily understood by its users and its users can find what they are looking for in a short time, and errors that occur are very minimal. This study aims to find out whether the website has been able to meet the needs of its users or not and whether the user experiences complications when using it or not. In Indonesia there are also many platforms that provide distribution or fundraising online and can be monitored for movement, such as example bookisa.com , this platform has been around since 2013 but it is still a social movement and it was only in 2014 that the book was switched to focus on online donations and in 2018 the book was able to channel more than 500 billion to those in need. This research uses the webuse method. The study analysed by sampling 20 people and the results of Good on the four variables, with the highest variable being Content, Organization, and Readability variable which got score 0.77, as well as the lowest variable is design user interface score of 0.70.